The Effectiveness of Interactive Multimedia-Based E-Moral Games in Teaching and Learning Moral Education - Salleh, Sakinah; Alwi, Ain Syafia Qutreenie; Yunus, Alwi Mohd (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
The Covid-19 pandemic has shifted teaching and learning from face-to-face to online platforms, requiring teachers to integrate interactive multimedia for effective delivery. This study examines students' readiness in using interactive multimedia and evaluates the effectiveness of e-Moral Games in teaching Moral Education. Using a qualitative approach, data were collected through interviews and library research. Seven teachers from four secondary schools in Perak, Penang, and Selangor participated in this study through purposive sampling.The findings indicate that e-Moral Games positively impact students' engagement and readiness, increasing their interest and comprehension. The interactive multimedia approach helps students stay focused and better understand moral concepts. Moreover, e-Moral Games are accessible and relevant, making them an effective tool for Moral Education. This study also highlights the benefits for teachers, as it enhances students' willingness to learn and improves instructional effectiveness. By incorporating diverse teaching methods, educators can create more engaging and meaningful learning experiences, ultimately fostering a more interactive and impactful learning environment.